Past references are insufficient for Latin American biodiversity conservation in the Anthropocene - Grau, Hector Ricardo (2024)
Often, Latin America conservation policy implicitly assumes past references to define worth-conserving ecosystems. However, the Pleistocene/pre-human reference is based on biophysical conditions impossible to be restored; the early Holocene reference overlooks that early humans likely caused massive extinctions; pre-European references fail to acknowledge that indigenous societies were often unsustainable and that many valuable ecosystems are in part a colonial legacy; pre-industrial references underplay the role of biological invasions, modern technology and socioeconomic development to preserve, increase or generate biodiversity. The Anthropocene rapid dynamics requires forward-looking policies that incorporate change as a source of biodiversity and resilience, actively accept that urbanization and modern agriculture can play a key role in conservation, challenge the prevalence of nativism and eco-alarmism, and emphasize that research should focus on shaping future socio-ecological scenarios, that would necessarily differ from the past.